Propensity Score-Matched Analysis of Lesion Patterns in Stroke Patients With Patent Foramen Ovale and Patients With Spontaneous Intracranial Artery Dissection - Huang, Yangyang; Cheng, Yifan; Shao, Bei; Zhou, Xuanyou; Liang, Huazheng; Zhuang, Jianhua; Bi, Yong (Frontiers in Neurology, 2019)
Aims：To investigate clinical and imaging features of stroke patients with patent foramen ovale (PFO) and those with spontaneous intracranial artery dissection (SIAD), and to obtain information about their etiological mechanisms of cerebral ischemia. Materials and methods: We retrospectively examined both clinical and imaging results of 40 stroke patients with PFO and 29 stroke patients with SIAD. To reduce selection bias, we conducted a propensity score-matching analysis. The patients’ propensity scores were estimated using a logistic regression model based on the following variables: age, sex, hypertension, diabetes mellitus, hypercholesterolemia, cigarette smoking, stroke histories and NIHSS score. We compared the pattern of cerebral DWI lesions between patients with PFO and those with SIAD. Results：After propensity score matching, 21 pairs of patients were compared. The clinical characteristics of the 2 groups were well matched. The distribution of DWI lesion patterns differed between the 2 groups. Single lesions (cortical or subcortical) were more frequent in the PFO group than in the SIAD group (P = 0.026). Multiple lesions in one vascular territory occurred more frequently in the SIAD group than in the PFO group (P = 0.035). Conclusion: The present study suggested that features of DWI of patients with PFO and SIAD might provide clues to the etiology of these patients. Single lesions (cortical or subcortical) might be a typical feature of PFO associated stroke, while multiple lesions in one vascular territory might be a specific feature of SIAD associated stroke.